ESG: Implementation, Reporting, and Internal Audit’s Role - Khattar, Rashi; Ramanathan, Gaytri; Kumar, Shalini (Management Journal for Advanced Research, 2025)
This paper explores the implementation, reporting, and role of internal audit in Environmental, Social, and Governance (ESG) practices within organizations. It examines the growing importance of ESG factors in corporate decision-making, the challenges associated with their implementation, and the role of internal audit in ensuring effective ESG reporting. A survey comprising nine questions was conducted, focusing on the Consumer Electronics, Metals and Mining, Automobile, and Chemical industries. The transition of ESG factors from conceptual and investor preferences to regulatory requirements presents challenges for all stakeholders, particularly in integrating sustainability risk factors into existing Risk Management Frameworks.